Respiratory Monitoring in Pediatric Neuromuscular Disease - Andre Sugiyono; Siti Chandra Widjanantie (Indonesian Journal of Physical Medicine & Rehabilitation, 2021)
ABSTRACTNeuromuscular disease in childhood result in dysfunction of chest wall and lung movement that interfereventilation function and gas exchange. Without vital respiratory pump, ventilation, gas exchangefunction and cough ability would be compromised and could result in complications such as pneumonia,atelectasis, and respiratory failure.Comorbid factors in cardiovascular, musculoskeletal, nutrition, and gastrointestinal could aggravaterespiratory morbidity and mortality if not adequately treated. This paper was written to reviewanatomy and physiology of neurorespiratory system, pathophysiology of respiratory complication inneuromuscular disease, clinical assessment and respiratory monitoring of childhood neuromusculardisease from Physical Medicine and Rehabilitation point of view .Keywords: assessment, neuromuscular disease, pediatric, respiratory, ventilation